Analisis Strategi Pemasaran Untuk Meningkatkan Penjualan Pada Usaha Ibu Bagas di Kecamatan Mamuju - Musyawarah, Irdha Yanti; Idayanti, Desi (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
The title of this research is an analysis of marketing strategies to increase sales at Mrs. Bagas' business in Mamuju District. This study aims to determine how the marketing strategy applied by Mrs. Bagas's business to increase sales. The data needed by the researcher uses the types of qualitative data and quantitative data. The data sources are primary data and secondary data. The method used in collecting the required data: Observation, Interview, Documentation and Literature Study. To find out how the strategy is used Swot Analysis Method (Strength, Weakness, Opportunity and Threat). From the results of the SWOT analysis, it was found that the EFAS (External Factor Analysis Summary) results obtained each value, for opportunities a value of 1.47 was obtained and a value of 0.64 for threats, this means that Ibu Bagas's business in Mamuju District has a greater opportunity value than threat value. The IFAS value for the strength and weakness variables each obtained a strength with a value of 1.66 while a weakness obtained a value of 0.86, this means that the strength of the Ibu Bagas Business in Mamuju District is greater than the value of its weakness. From the results of the SWOT analysis diagram, it is found that the position of Ibu Bagas's business in Mamuju District has opportunities and strengths so that it can take advantage of existing opportunities. The strategy that must be applied in this condition is to support an aggressive growth policy.